2019
DOI: 10.1108/prt-12-2017-0101
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing of non-fibrous textile for production of high performance easy-care cotton fabrics

Abstract: Purpose This study aims to explore the incorporation of starch nanoparticles (SNPs) in cross-linking formulation of cotton fabrics to see their impact on fabric performance like tensile strength, dry wrinkle recovery angles, elongation at break, degree of whiteness and increase in weight as well as durability. Design/methodology/approach SNPs of size around 80-100 nm were successfully prepared from native maize starch by Nano precipitation technique and confirmed instrumentally by scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…The opposite holds true for tensile strength and elongation at break that is in full agreement with what would be anticipated. Previous reports [23][24][25] revealed that tensile strength stands as an inverse function of wrinkle recovery angle. At the same time, tensile strength values of the finished cotton fabrics in the presence of CNPs are higher than that finished in the absence of it, which noticeably reveals the outstanding effect of adding chitosan nanoparticles during durable press finishing of cotton textile as a reinforcing agent of cotton cellulose during the finishing process.…”
Section: Citric Acid Concentrationmentioning
confidence: 94%
“…The opposite holds true for tensile strength and elongation at break that is in full agreement with what would be anticipated. Previous reports [23][24][25] revealed that tensile strength stands as an inverse function of wrinkle recovery angle. At the same time, tensile strength values of the finished cotton fabrics in the presence of CNPs are higher than that finished in the absence of it, which noticeably reveals the outstanding effect of adding chitosan nanoparticles during durable press finishing of cotton textile as a reinforcing agent of cotton cellulose during the finishing process.…”
Section: Citric Acid Concentrationmentioning
confidence: 94%
“…Our previously prepared SNPs of size around 80–100 nm after fully characterized using world class facilities that were prepared by nano precipitation technique followed by freeze-drying as reported in our previous work [9] were used throughout the work. Details of the conditions used for SNPs preparation, properties and characterization after freeze drying are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, more efficient cross-linking agents that can produce multi-functional properties to finished fabrics are still in demand. In addition, the currently reported cellulose cross-linking agents have some undesirable effects on strength properties and proposing a cross-linking agent with no diverse impact on treated fabrics is still a challenge [9]. For example, the strength properties of the cotton fabrics treated with cross-linking agents (chemical finish) are considerably reduced up to 60% as a result of this finishing process, which is considered as a major deficiency of cross-linking agents [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Citric acid is safe in process and use and can be applied easily and economically on textile fabrics. It is one of the poly carboxylic acids which have been used as a substitution for formaldehyde releasing conventional N-methylol compounds especially in durable press finishing processes to impart ease and care characteristics especially for wrinkle resistance in presence of sodium hypophosphite as a potential catalyst for ester crosslinking (Mostafa et al , 2019; Morsy et al , 2019; Welch and Kottes Andrews, 1989; Choi et al , 1993; Schramm et al , 2002). However, there are a limited reports about the possibility of imparting desirable anti-bacterial activity, ease and care and reinforcement functionalities to the viscose fabric using a proper an echo-friendly finishing technique (Mostafa et al , 2019; Morsy et al , 2019; Mostafa et al , 2020; Mostafa and El-Sanabary, 2020; Roy Choudhury, 2017; Ibrahim et al , 2018).…”
Section: Introductionmentioning
confidence: 99%